2005
DOI: 10.1136/hrt.2004.055046
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction caused by a septic coronary embolism diagnosed and treated with a thrombectomy catheter

Abstract: Acute myocardial infarctions are common in bacteraemia but are seldom diagnosed during life. A 64 year old man with severe chest pain who had fever for several days due to possible bacteraemia was shown by ECG and echocardiography to have possible lateral infarction. Immediate coronary angiography showed possible thrombus in the left circumflex artery, which was treated by thrombectomy catheter. Bacterial thrombus was removed and was verified by histological examination. A stent was implanted without complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…2 In the era of primary percutaneous coronary intervention (PCI) for AMI, thrombectomy devices are increasingly used and histological examination of the aspirated thrombus provides additional information for diagnosing CE. 3 Because the majority of previous reports describing the clinical characteristics of CE were case reports with a small number of patients, [3][4][5][6][7][8][9][10][11][12][13][14][15] with the largest series to date consisting of 55 patients in an autopsy study 2 and 14 patients with probable CE in the clinical setting, 16 a mechanistic study for this important cause of AMI is now warranted.…”
mentioning
confidence: 99%
“…2 In the era of primary percutaneous coronary intervention (PCI) for AMI, thrombectomy devices are increasingly used and histological examination of the aspirated thrombus provides additional information for diagnosing CE. 3 Because the majority of previous reports describing the clinical characteristics of CE were case reports with a small number of patients, [3][4][5][6][7][8][9][10][11][12][13][14][15] with the largest series to date consisting of 55 patients in an autopsy study 2 and 14 patients with probable CE in the clinical setting, 16 a mechanistic study for this important cause of AMI is now warranted.…”
mentioning
confidence: 99%
“…Treatment options include intravenous or intracoronary thrombolytic therapy, percutaneous catheter aspiration embolectomy followed in some cases by balloon angioplasty with or without stenting, and medical management with anti-coagulants and IIb-IIIa inhibitors (8-11). Taniike et al reported a case of non-STEMI caused by bacterial embolism in proximal LCX that was treated with manual thrombectomy and stenting (12). Yuce et al reported another case of non-STEMI as a result of thromboembolism in distal RCA in a patient with prosthetic mitral valve thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Histological examination of the retrieved material in this case revealed severe calcified atherosclerotic plaque without thrombotic components. Several reports demonstrated a free-floating thrombus in ascending aorta [6], and bacterial thrombi [7] were rare coronary emboli sources. However, there are no reports which demonstrated calcified aortic plaque caused coronary emboli as this case.…”
Section: Discussionmentioning
confidence: 99%